Superior organic dye removal by CoCr2O4 nanoparticles: Adsorption kinetics and isotherm - Pham Kim Ngoc (Journal of Science: Advanced Materials and Devices, 2022)
In the present work, we report on the dye removal efficiency of Cobalt chromite, CoCr2O4 nanoparticles synthesized via the solvothermal method. The obtained CoCr2O4 nanoparticles demonstrated that the dye removal efficiency of CoCr2O4 nanoparticles could be enhanced by a reduction of size or improved water dispersibility. The pseudo-second-order kinetic model best describes the adsorption of Congo red (CR) dye on CoCr2O4 nanoparticles. The Langmuir adsorption isotherm model fitted best for the adsorption process and the adsorption capacity for CCO@450 and CCO@550 nanoparticles were found to be 59.4 and 43.8 mg g−1, respectively. Dye adsorption studies on a mixture of CR, MB, and RhB dyes solution revealed that the MB removal efficiency of CoCr2O4 nanoparticles could improve to 81% compared to 55% in solo MB solution. With the ease of use, high stability, diverse working environment, and superior adsorption capacity, CoCr2O4 nanoparticles have the potential to be used as an organic dye removal adsorbent for wastewater treatment.